Through a Screen Darkly: Use of Computer-Mediated Communication Predicts Emotional Functioning. Issue 6 (December 2020) - Myruski, Sarah; Quintero, Jean M.; Denefrio, Samantha; Dennis-Tiwary, Tracy A.
Despite the pervasive use of computer-mediated communication, relatively little is known about its implications for emotional adjustment. Recent studies suggest that a preference for computer-mediated communication over other types of communication is associated with emotional vulnerabilities, and its active forms (e.g., direct communication) confer psychosocial benefits compared its passive forms (e.g., browsing Facebook). In this study, we simultaneously examined quality, quantity, and preferences for computer-mediated communication in relation to emotional competencies (emotion detection and regulation) and emotional well-being (self-report of mood and anxiety symptoms). In Study 1, participants ( N  = 123) completed a facial morphing task, a computerized assessment of the speed and accuracy of emotion detection, and the Social Media and Communication Questionnaire assessing quantity and preferences to communicate via computer-mediated communication versus face-to-face. More use of computer-mediated communication along with preferring it for casual communication, was associated with faster and more accurate emotion detection. More use of computer-mediated communication, along with preferring it for positive communication and expressing distress, was associated with more difficulties with emotion regulation. Study 2 ( N  = 32) added a task-based assessment of active and passive Facebook use in relation to measures of emotional functioning in Study 1. More active Facebook use was associated with greater emotional well-being, whereas more passive Facebook use was associated with less emotional well-being. Active and passive Facebook use was not significantly associated with self-report of broader computer-mediated communication preferences. Together, results suggest that greater use and preference for computer-mediated versus face-to-face communication may be related to heightened emotional sensitivity and more problems with emotion regulation, yet active versus passive use may serve to bolster emotional well-being.